Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2022
DOI: 10.18653/v1/2022.acl-long.213
|View full text |Cite
|
Sign up to set email alerts
|

ProtoTEx: Explaining Model Decisions with Prototype Tensors

Abstract: We present PROTOTEX, a novel white-box NLP classification architecture based on prototype networks (Li et al., 2018). PROTOTEX faithfully explains model decisions based on prototype tensors that encode latent clusters of training examples. At inference time, classification decisions are based on the distances between the input text and the prototype tensors, explained via the training examples most similar to the most influential prototypes. We also describe a novel interleaved training algorithm that effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Explaining the veracity can also be formulated as a summarization problem over the gathered evidence to explain a fact-check (Atanasova, Simonsen, Lioma and Augenstein, 2020a;Kotonya and Toni, 2020b). Finally, case-based explanations can provide the user with similar, human-labeled instances (Das, Gupta, Kovatchev, Lease and Li, 2022).…”
Section: Explaining Veracity Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explaining the veracity can also be formulated as a summarization problem over the gathered evidence to explain a fact-check (Atanasova, Simonsen, Lioma and Augenstein, 2020a;Kotonya and Toni, 2020b). Finally, case-based explanations can provide the user with similar, human-labeled instances (Das, Gupta, Kovatchev, Lease and Li, 2022).…”
Section: Explaining Veracity Predictionmentioning
confidence: 99%
“…As explainable NLP develops, automated fact-checking tasks also need to evolve and provide explanations that are accessible to human stakeholders yet faithful to the underlying model. For example, case-based explanations are mostly unexplored in automated fact-checking, although working systems have been proposed for propaganda detection (Das et al, 2022).…”
Section: Veracity Prediction and Explanationmentioning
confidence: 99%
“…Hence, it is beneficial to encourage prototype segregation, that is, a broader projection onto the dataset and a more diverse representation of different samples. Besides normalizing prototype distances, which has been shown to influence prototype segregation (Das et al, 2022), proto-lm introduces an additional hyperparameter, K. This parameter controls the number of prototypes that each training example associates and disassociates with during training. As changing K also influences the decision-making process of the model by altering the number of samples the models compare for each input, we examine the impact of K on both prototype segregation and model performance.…”
Section: Prototype Uniqueness and Performancementioning
confidence: 99%
“…We employ workers from Amazon Mechanical Turk to crowdsource our evaluations and presented 3 workers with 50 examples each from the SST2 and QNLI datasets, along with explanations for the model's decisions in the settings mentioned in §5.2. We use the best performing models for SST2 and QNLI (those presented in Table 1), since previous studies found that the utility of PE's are reliant on model accuracy (Das et al, 2022). Additionally, we assess the accuracy of the human annotators in relation to the ground truth labels.…”
Section: Simulatability Experimentsmentioning
confidence: 99%
“…We adapt their idea and show how to apply it to clinical natural language. Recently, Ming et al (2019) and Das et al (2022) applied the concept of prototypical networks to text classification and showed how prototypical texts help to interpret predictions. In contrast to their work and following Chen et al (2019), we identify prototypical parts rather than whole documents by using label-wise attention.…”
Section: Manual Analysis By Medical Doctorsmentioning
confidence: 99%